Secular trends in pediatric antiretroviral treatment programs in rural and urban Zambia: a retrospective cohort study - Cotham Matt; van Dijk Janneke H; Bolton-Moore Carolyn; Sutcliffe Catherine G; Tambatamba Bushimbwa; Moss William J (BMC, 2010)
Abstract Background Since 2003 pediatric antiretroviral treatment (ART) programs have scaled-up in sub-Saharan Africa and should be evaluated to assess progress and identify areas for improvement. We evaluated secular trends in the characteristics and treatment outcomes of children in three pediatric ART clinics in urban and rural areas in Zambia. Methods Routinely collected data were analyzed from three ART programs in rural (Macha and Mukinge) and urban (Lusaka) Zambia between program implementation and July 2008. Data were obtained from electronic medical record systems and medical record abstraction, and were categorized by year of program implementation. Characteristics of all HIV-infected and exposed children enrolled in the programs and all children initiating treatment were compared by year of implementation. Results Age decreased and immunologic characteristics improved in all groups over time in both urban and rural clinics, with greater improvement observed in the rural clinics. Among children both eligible and ineligible for ART at clinic enrollment, the majority started treatment within a year. A high proportion of children, particularly those ineligible for ART at clinic enrollment, were lost to follow-up prior to initiating ART. Among children initiating ART, clinical and immunologic outcomes after six months of treatment improved in both urban and rural clinics. In the urban clinics, mortality after six months of treatment declined with program duration, and in the rural clinics, the proportion of children defaulting by six months increased with program duration. Conclusions Treatment programs are showing signs of progress in the care of HIV-infected children, particularly in the rural clinics where scale-up increased rapidly over the first three years of program implementation. However, continued efforts to optimize care are needed as many children continue to enroll in ART programs at a late stage of disease and thus are not receiving the full benefits of treatment.